Seroepidemiological surveillance of SARS-CoV-2 circulation in 41 municipalities in Honduras with no report of active cases, COVID-19, June 16-23, 2020 - Mejía Núñez, Mario Rene (2020)
Introduction: In Honduras on March 12, 2020, the first case of COVID-19 caused by the SARS-CoV-2 was reported. From that moment on, a series of measures were adopted to slow down contact throughout the country. By June 2020, cases are reported across the whole country. With the objective of identifying the presence and circulation of SARS-CoV-2, characterizing and identifying suggestive symptoms of COVID-19 in the population, the present study was carried out. Methodology: A descriptive cross-sectional study was carried out, using a quantitative and qualitative approach, using the LQAS sampling method. The study population was the inhabitants of the identified municipalities, with no current circulation data for SARS-CoV-2 or the municipalities whose last confirmed case was 21 days ago. The data was collected through an electronic survey, it was possible to apply rapid antibody detection tests (IgG and IgM). Results: 792 people from 41 municipalities of the country were surveyed and tested. Positivity of contact was found in 6.2% (49/792). Of these, 55.1% (27/49) are men. 61.2% (30/49) are between 20 and 49 years old. The clinical symptoms found were fever, decreased appetite, respiratory distress, and loss of taste and smell, the 49.2% (32/49) without symptoms. Conclusions: virus circulation was demonstrated in the population of municipalities in which no cases were officially reported and after 96 days of the first confirmed case in the country. Detection of virus-specific antibodies could be important in surveys for asymptomatic infection in areas where contact is expected.